Modelling of generating equipment operation and reliability - Mromliński, L. (Видавництво Національного університету «Львівська політехніка», 2003)
Operation properties of generating equipment are characterized by the following parameters: mean values of time to failure and to repair and the corresponding failure and repair intensities. Reliability may be expressed by the unit forced outage rate. These parameters are determined using the statistical analysis for the set of generating units located in one power plant. The results of analysis demonstrate the necessity of treating the units individually in spite of their similar technical construction.